PENGARUH KEPEMIMPINAN TRANSAKSIONAL DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PT. SUMBER ABADI SENTRATAMA PONTIANAK - B31110006, Fengki (Jurnal Manajemen Update, 2015)
Leadership has a major role in the development of the company as well as improving employee performance. The development of existing companies must determine the appropriate strategy in implementing the leadership, because the leadership process will be effect of employee performance. Therefore, leaders must look ahead what should be improve and what should be preserved. The purpose of this study was to test and analyze the transactional leadership and the transformational leadership on employee performance and was to test and analyze the differences of employee performance by age and year of service at PT. Sumber Abadi Sentratama Pontianak. Research type is quantitative, reasearch method is causality, uses multiple regression analysis. The samples of this study is 57  employee. The result showed Transactional Leadership and Transformational Leadership has a  positive and significant effect to the employe performance,   there is no significant performance difference between employees based on the age of employee and there is a significant difference in performance based on the period of employment. This company should be able to increase the overall leadership role that will be improve the employee performance and will improve the company’s image in the eyes of the public and consumers. Keywords: Transactional Leadership, Transformational Leadership, Employee Performance, Age of Employee, Period of Employment.